Reverence and Teaching: The Forgotten Virtue. Issue 13 (December 2013) - Garrison, Jim; Rud, A. G.
The purpose of this chapter is to understand the spiritual dimensions of teaching by elucidating the cardinal and forgotten virtue of reverence. Reverence has a power beyond a typical understanding of it as something religious. Reverence involves a sense of wonder and awe for something or someone that meets at least one of the following conditions: (1) something we cannot control; (2) something we cannot create; (3) something we cannot fully understand; (4) something transcendent, even supernatural The chapter shows reverence in a wider context that does not diminish its spiritual connotations, but rather shows its importance and relevance to teaching in today's classrooms.